2019
DOI: 10.7874/jao.2018.00549
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic versus Endoscopic Inlay Butterfly Cartilage Tympanoplasty

Abstract: Background and Objectives Inlay butterfly cartilage tympanoplasty makes the graft easy, and reduces operating time. The present study aimed to investigate the outcomes of microscopic versus endoscopic inlay butterfly cartilage tympanoplasty. Subjects and Methods In this retrospective study, the outcomes of 63 patients who underwent inlay butterfly cartilage tympanoplasty with small to medium chronic tympanic membrane perforation were evaluated. Twenty-four patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…In view of the audiological outcome, the mean AC threshold and ABG improved significantly regardless of the perforation size and location. A significant correlation between the preoperative size of the TM perforation and the postoperative ABG was reported in a recent study [16], and it was easy to predict that the patients with larger perforations would show bigger postoperative ABGs. To evaluate the exclusive effect of FGM among different size and location groups, we analyzed our hearing gain of FGM based on “ABG improvement” rather than postoperative ABG.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In view of the audiological outcome, the mean AC threshold and ABG improved significantly regardless of the perforation size and location. A significant correlation between the preoperative size of the TM perforation and the postoperative ABG was reported in a recent study [16], and it was easy to predict that the patients with larger perforations would show bigger postoperative ABGs. To evaluate the exclusive effect of FGM among different size and location groups, we analyzed our hearing gain of FGM based on “ABG improvement” rather than postoperative ABG.…”
Section: Discussionmentioning
confidence: 97%
“…FGM and inlay butterfly cartilage tympanoplasty is one of the alternative options for conventional tympanoplasty [15, 16]. Compared to inlay butterfly cartilage tympanoplasty, which usually uses tragal cartilage as a graft material, FGM is relatively less invasive, and fat has some advantages in that it can be harvested easily and several times, unlike tragal cartilages.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline characteristics of the included studies are presented in Table 1. The 43 studies enrolled a total of 3712 patients who received type I tympanoplasty 17‐59 . The follow‐up duration ranged from 3 to 23.2 months.…”
Section: Resultsmentioning
confidence: 99%
“…James (6) looked at the outcomes of 250 pediatric patients and found an overall closure rate of 88%, again with no difference between the TEES and MT groups. Multiple studies that look at both pediatric and adult patients have found similar closure rates between 72 and 97% (7–12), with no differences between TEES and MT.…”
Section: Discussionmentioning
confidence: 96%